The Role of HR Quality and Work Discipline in Improving the Motivation and Performance of District Court Employees - Mu’ah Mu’ah; Yulia Firdawati; Mas’adah Mas’adah; Masram Masram; Nurul Qomariah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
Human resources are a very important component in an organization. The success or failure of an organization depends on the human resources in an organization. This study aims to examine and analyze the quality of human resources and work discipline on the motivation and performance of employees at the Lamongan High Court. This research was conducted at the Lamongan District Court with a total of 35 employees, all of whom were used as samples (total sampling). Data were analyzed using the Partial Least Square (PLS) approach with SmartPLS 3.0 software. The results showed that the quality of human resources and work discipline had a significant effect on both work motivation and employee performance at the Lamongan District Court employees. Work motivation has no significant impact on employee performance. The results of the study as a whole provide implications that if the quality of human resources and work discipline possessed by the state civil apparatus is even better, it will have an influence on improving employee performance.